Soft tissue infections from fish spike wounds: normal commensal bacteria are more common than marine pathogens. Issue 1 (20th March 2017) - Collins, Hannah; Lee, Kin Mun; Cheng, Paul T.‐Y.; Hulme, Sarah
Abstract : Background: A fish spike injury can be sustained by anyone handling fish; during fishing, meal preparation or in retail. Case reports of fish spikes inoculating victims with virulent marine‐specific pathogens and causing systemic illness led us to question whether empirical treatment of these injuries with amoxicillin and clavulanic acid is adequate. Methods: This 2‐year prospective observational study was conducted at Middlemore Hospital, Auckland, New Zealand. Wound swabs and tissue samples belonging to patients presenting to the Department of Plastic and Reconstructive Surgery with an upper limb fish spike injury were sent to the laboratory ( n = 60). A series of stains and cultures were performed to look specifically for marine bacteria not typically isolated in other soft tissue injuries. Patient demographic data and injury details were collected. Results: Of the patients with adequate microbiology samples, 12% (6/50) grew clinically relevant bacteria resistant to amoxicillin and clavulanic acid. These included methicillin‐resistant Staphylococcus aureus (8%, 4/50), Enterobacter cloacae (2%, 1/50) and an anaerobic sporing bacillus (2%, 1/50). Only one patient grew a true marine‐specific bacteria, Photobacterium damselae, which was susceptible to amoxicillin and clavulanic acid. Conclusion: The authors concluded that amoxicillin and clavulanic acid is an adequate first‐line antibiotic for fish spike injuries but that flucloxacillin may be more appropriate given most bacteria were from patients' own skin flora. The authors suggest that clinicians consider the presence of resistant marine‐specific bacteria in cases where there is sepsis or inadequate response to initial therapy.